Seven plus initiative: the way forward to stem Dengue - Kumar, Santosh; Job, Sheen (Indian Journal of Community Health, 2020)
The vector-borne disease has been a public health challenge in the country since long. The menace of dengue, every rainy season only draws attention towards the need for community participation to combat this problem. Dengue has come out to be a social problem which mostly depends upon the environment and habitation of humans. The overwhelming concern over the increasing burden and its dire consequences, a multidisciplinary team was constituted which comprised of local leaders, ASHA, ANM and NGOs, destined to encourage community participation for dengue prevention. A seven-plus initiative was started by this multidisciplinary team which aims to mitigate the larva life cycle of dengue from the breeding site in seven days. This initiative was completely based on active surveillance of breeding sites, tracking fever cases and active implementation of source reduction measures coupled with insecticide spray.